The relationship between mental health, cultural beliefs and sexual behavior of pregnant women - Malekzadeh, Setareh; Ahadi, Hassan; Dortaj, Fariborz (Researcher Bulletin of Medical Sciences, 2022)
The aim of this study was to investigate the relationship between mental health and cultural beliefs and sexual behavior in pregnant women. Mental health and cultural beliefs are important individual factors. Human sexual behaviors are influenced by culture, customs, beliefs and beliefs of people, and there is a lot of diversity in different societies. This study was a field correlation and the study sample was available to 100 pregnant women. Sampling method: Sampling was done through a questionnaire. The results showed that cultural beliefs of individuals had an effect on their sexual behavior and women's mental health had a significant relationship with the request of unusual sexual behaviors by their husbands.